INVENTARISASI UMKM IKAN PINDANG DI DUSUN PENGAWISAN DESA SEKOTONG BARAT, KECAMATAN SEKOTONG, LOMBOK BARAT - Amalia, Asti; Diniarti, Nanda; Maulidina, Eva; S., Ega; Puspita, Nurhidayah; Wulaningsih, Nabila; Helviana, Ima (Jurnal Wicara, 2025)
The community inventory activity in Pengawisan Hamlet, West Sekotong Village, Sekotong District, West Lombok, is part of the KKN-MBKM program which aims The purpose of this activity is to identify the process and production capacity of pindang tuna in Pengawisan Hamlet, to find out the obstacles faced such as raw materials, technology, and marketing, and to encourage innovation and mentoring so that the business can grow, be competitive, and improve the welfare of coastal communities. The method used is a qualitative method with data collection and documentation. The inventory results show that the raw materials are obtained from local fishermen, then processed by smoking using fresh water and salt so that the quality of the fish is maintained and more durable. There are 3 groups of managers of Pindang Tuna MSMEs, consisting of 2-5 people in one group. Where the smallest group has 2 processors and the processed output is 40 baskets/day. For the medium processing group there are 4 processors with the processed output of 100 baskets/day. Meanwhile, the largest processing group consists of five people, producing 280 baskets per day, with the highest distribution at around 40% in the Baretais market. This business adds value to the fishermen's catch and provides a significant source of income for the fish processing community in Pengawisan Hamlet.